Comparison of Varenicline’s Effectiveness with Nicotin Replacement Therapy (NRT) or A Combination of Both in Smoking Cessation: Literature Review - Mahardika Urbaningrum, Lestari; Laily Hilmi, Indah (Sean Institute, 2022)
Smoking is a cause of many chronic diseases such as lung cancer, oral cancer, to cardiovascular disease. Smoking addiction is caused by the nicotine in cigarettes. Thus Nicotine Replacement Therapy (NRT) was created as a substitute for nicotine consumption without smoking. While another drug that is widely prescribed is varenicline. However, varenicline is not yet available in Indonesia and the use of NRT is still very rare. Therefore, research is needed to compare the efficacy of the two. The research was conducted by studying the literature of international journals and obtained 12 journals that match the research title. As a result, varenicline monotherapy proved to be more effective than NRT or a combination of both.